Polydatin Attenuates Neuronal Loss via Reducing Neuroinflammation and Oxidative Stress in Rat MCAO Models - Shah, Fawad Ali; Kury, Lina Al; Li, Tao; Zeb, Alam; Koh, Phil Ok; Liu, Fang; Zhou, Qiang; Hussain, Ishtiaq; Khan, Arif Ullah; Jiang, Yuhua; Li, Shupeng (Frontiers in Pharmacology, 2019)
Background: Ischemic stroke is characterized by permanent or transient obstruction of blood flow, which initiates a cascading pathological process, starting from acute ATP loss and ionic imbalance to subsequent membrane depolarization, glutamate excitotoxicity, and calcium overload. These initial events are followed by neuroinflammation and oxidative stress, eventually causing neuronal neurosis and apoptosis. Previous endeavors aiming at the initial transient stages of stroke pathology have resulted in repeated failures in clinical trials. In the present study, the effects of polydatin were examined for its possible effects on other ischemic related pathological changes. Methods: Adult male Sprague–Dawley rats underwent permanent middle cerebral artery occlusion, and were administered intraperitoneally two doses of 30mg/kg polydatin or vehicle 30 min before and 1 h after ischemia. Neurobehavioral tests were performed to assess their neurological deficits. TTC staining, immunohistochemistry, and immunofluorescent experiments were conducted to examine the neuronal cell loss, protein expression and localization. Western blot analysis was performed to assess the protein levels. Results: Our results demonstrated that polydatin treatment reduced the infarction volume and mitigated the neurobehavioral deficits, sequentially rescued neuronal apoptosis. Ischemic stroke induced an elevation of neuroinflammation and reactive oxygen species, which could be attenuated by polydatin via the reduced activation of p38 mitogen-activated protein kinase and c-Jun N-terminal kinase. In addition, polydatin upregulated the endogenous antioxidant nuclear factor erythroid 2-related factor 2, heme oxygenase-1, the thioredoxin pathway, and eventually reversed ischemic-stroke-induced elevation of ROS and inflammation in ischemic cortical tissue. Conclusions: The diverse and broad actions of polydatin suggested that it could be a multiple targeting neuroprotective agent in ameliorating the detrimental effects of MCAO, such as neuroinflammation, oxidative stress and neuronal apoptosis. As repetitive clinical trials of neuroprotectants targeting a single step of stroke pathological process have failed previously, our results suggested that a neuroprotective strategy of acting at different stages may be more advantageous to intervene in the vicious cycles in MCAO.